shasjing is correct but perhaps a little short on the explanation:
4(sinx*cosx-cosx)=4*sinx*(cosx-1) and the Taylor series are sin(x)=x+ other stuff while cos(x)=1-x^2/2+other stuff so 4*sinx*(cosx-1) is about 4*x*-x^2/2 which is -2x^3. then -2x^3/x^2 = -2x -> 0 as x -> 0.
If you don't use Taylor's series you are going to have to do L'Hopital rule,,,,,,,,,,
2006-12-27 05:53:29
·
answer #1
·
answered by a_math_guy 5
·
0⤊
0⤋
The answer is zero because sinx cosx - sin x has higher order of zero than x^2.
2006-12-27 05:26:03
·
answer #2
·
answered by sahsjing 7
·
0⤊
0⤋
the sole interior the hold close bathing room is a 0. The seat is unfastened and it has 2 push buttons for flushing. One for low ability, one for good. I hate it. i make the main the sole interior the concentrated customer bathing room and this is a fascinating 10. It has a take care of! is purely not waiting to attend to pass living house and use it!
2016-12-11 17:00:17
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Thus 2(sin2x –2sinx) / x^2 ={l’hopital} = (2cos2x –2cosx) / x = {l’hopital} = -4sin2x +2sinx =0;
2006-12-27 08:30:19
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋